CagA status and VacA subtypes of Helicobacter pylori in relation to histopathologic findings in Iranian population - Molaei Mahsa; Foroughi Forough; Mashayekhi Reza; Haghazali Mehrdad; Zojaji Homayoon; Jafari Fereshteh; Dabiri Hossein; Zali Mohammad Reza (Wolters Kluwer Medknow Publications, 2010)
Background/Objective: The aim of this study was to detect dominant cagA/vacA genotypes of Helicobacter Pylori (H. pylori) and determine correlations between different cagA/vacA genotypes and histologic features of chronic gastritis in Iranian patients. Methods: Gastric biopsy was taken from 166 patients with nonulcer dyspepsia. The specimens were processed and DNA from each H. pylori isolate was extracted from multiple colony sweeps for identification of glmM gene. The vacA subtypes and cagA gene were tested by PCR . Histopathological features were recorded and graded according to partial Sydney system. Results: Of the 86 strains, 66 (76.7%) were cagA positive. The proportions of vacA gene subtypes s1, s2, m1 and m2 in the 78 strains isolated were 70.5%, 29.5%, 37.2% and 62.8%, respectively. About 83.3% of the vacA-positive strains had s1 allele. Twenty-six strains (33.3%) were positive for both cagA and m1 allele. Positive cagA status and vacA subtypes were not associated significantly with presence of neutrophil infiltration, intestinal metaplasia or H. pylori density. Only vacA s1 was significantly associated with more severe inflammation (P=0.02). The dominant genotype of H. pylori was vacA plus s1/m2. CagA gene positivity rate was not closely associated with severity of the disease. Conclusion: H. pylori strains showing vacA s1 genotype were associated with more severe gastritis. These findings show that vacA genotyping may have clinical relevance in Iran.